THE EFFECT OF PQRST (PREVIEW, QUESTION, READ, SUMMARY, AND TEST) STRATEGY ON READING COMPREHENSION AT FIRST-GRADE STUDENTS OF SMAN 1 SABAK AUH SIAK - Ratna Arbandari; Fadly Azhar; Erni Erni (JURNAL PAJAR (Pendidikan dan Pengajaran), 2022)
This paper discusses an experimental research study regarding the effect of PQRST (Preview, Question, Read, Summary, and Test) strategy on reading comprehension of the first-year students at SMAN 1 of Sabak Auh Siak. The study shows that 65% of the students have difficulties in comprehending the reading passage about a descriptive text. Based on the students’ reading indicators, it can be identified that they have difficulties in determining the main idea, locating references, understanding vocabulary, making inferences, and finding detailed information. This study uses a quantitative method on a true experimental design of two groups of first-year students using pre-test and post-test. The study involves 44 students, divided into two classes: the control class with 21 students and the experimental class with 23 students. The instrument is a test that consists of questions with multiple choices and four options (A/B/C/D). In order to analyze the data formula, statistical software namely SPSS version 23 is used to analyze the results of the study. The significant effect of PQRST (Preview, Question, Read, Summary, and Test) strategy on reading comprehension at the first-year students of SMAN 1 Sabak Auh in Kabupaten Siak (2-tailed) is. 000 ˂ .005, which means that the H0 is rejected, while Ha is accepted. Thus, there is a significant effect on first-year students' reading comprehension in descriptive text between the students who are taught by applying the PQRST strategy and those who are not.